2013
DOI: 10.1111/jce.12207
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Denervation as an Adjunct to Catheter Ablation for the Treatment of Ventricular Electrical Storm in the Setting of Acute Myocardial Infarction

Abstract: We present a case of ventricular storm (VS) in a patient with acute ST-elevation myocardial infarction (STEMI). After initial successful thrombus extraction and percutaneous coronary intervention (PCI) of the proximal left anterior descending (LAD) coronary artery, a 63-year-old male patient showed recurrent monomorphic ventricular tachycardia (VT) and fibrillation (VF) episodes refractory to antiarrhythmic drug therapy. After initial successful VT ablation, fast VT and VF episodes remained an evident problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…This suggests that the sympathetic nervous system might play an important role in the genesis and maintenance of VA in AMI patients. Direct inhibition of sympathetic nerve activity, for instance, by renal denervation or high thoracic epidural anesthesia, drastically decreases VA incidence after AMI in animal models and in clinical patients [13][14][15][16]. These studies indicate that, in beta-blocker intolerant or contraindicated patients, denervation is an alternative approach to prevent VA occurrence.…”
Section: Introductionmentioning
confidence: 91%
“…This suggests that the sympathetic nervous system might play an important role in the genesis and maintenance of VA in AMI patients. Direct inhibition of sympathetic nerve activity, for instance, by renal denervation or high thoracic epidural anesthesia, drastically decreases VA incidence after AMI in animal models and in clinical patients [13][14][15][16]. These studies indicate that, in beta-blocker intolerant or contraindicated patients, denervation is an alternative approach to prevent VA occurrence.…”
Section: Introductionmentioning
confidence: 91%
“…Only one more VT episode that required implantable cardioverter defibrillator therapy recurred during a 5-month follow-up. Before that, similar attempts were made by Ukena et al [2], Hoffmann et al [3], and Remo et al [4], who showed that RDN was an effective and safe approach to the treatment of ischemic or nonischemic electrical storm. However, the underlying mechanisms and the potential role of kidney in the generation of ventricular arrhythmias (VAs) and sudden cardiac death (SCD) remain unclear.…”
mentioning
confidence: 78%
“…In particular, Hoffmann et al [31], presented the case of a 63-year-old male patient with ST elevation myocardial…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…After the initial treatment, the patient developed recurrent monomorphic VT and VF episodes (electrical storms) refractory to antiarrhythmic drug therapy that recurred after VT ablation. Due to the increasing instability RDN was urgently performed and the frequency of episodes significantly decreased while the patient remained free of VT/VF episodes after the day 23 of hospitalization [31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%